Educational process and socio-environmental conflicts: construction of possible meanings and senses - Santos, Romualdo Jose dos [UNESP]; Carvalho, Luiz Marcelo de [UNESP] (Univ Pedagogica & Tecnologica Colombia, 2021)
In this article, we systematize part of the results of the first author's thesis, which aimed to build possible meanings and senses on the relationship between the educational process and socioenvironmental conflicts, based on the analysis of theses and dissertations in environmental education [EE] carried out in Brazil. It is a documentary research integrated in a wider project about the state of the art of EE research in Brazil-EArte Project. The analyzed works were selected from the Thesis and Dissertations Bank available at the website of this project- www.earte.net. The analyses were guided by the theoretical-methodological referents associated with the historical-cultural perspective and with the Bakhtinian perspective. The data presented in this article refer to the analysis of theses and dissertations that explored educational processes involving socio-environmental conflicts, associated with the idea of participation and participation and citizenship. The analyses allowed us to consider that the promotion of participation and the exercise of citizenship have been understood as challenging tasks for environmental teachers. In this context, socio-environmental conflicts are currently considered as guiding principles of the proposals and practices of EE from a critical perspective, based on the dialogue between different types of knowledge, potentially capable of promoting the overcoming of the semi-training of the subjects.
Keywords: environmental education; citizenship; socio-environmental conflicts; participation; theses and dissertations